An Empirical Analysis of Interest Rate and Domestic Savings in Bangladesh (Global Journal of Human-Social Science, 2021)
The study investigates the relationship between deposit interest rate and gross savings in Bangladesh for the period 1976-2019. In this study, I used the ARDL approach to estimate the short run and long-run relationship between dependent and independent variables, which applicable if some variables are integrated of order one, and some are zero. The result of the study reveals that in the short-run impact of interest rate on gross saving is insignificantly negative, but in the long run this impact is insignificantly positive. The result also shows that both in the short-and the long-run, inflation and GDP positively impact the gross savings. Moreover, the impact of remittance on gross savings is positive in the short run and negative in the long run.
Keywords: deposit interest rate; gross saving; ardl; co-integration